"Less is more": A dose-response account of intranasal oxytocin pharmacodynamics in the human brain. (April 2022) - Martins, Daniel; Brodmann, Katja; Veronese, Mattia; Dipasquale, Ottavia; Mazibuko, Ndaba; Schuschnig, Uwe; Zelaya, Fernando; Fotopoulou, Aikaterini; Paloyelis, Yannis
Abstract: Intranasal oxytocin is attracting attention as a potential treatment for several brain disorders due to promising preclinical results. However, translating findings to humans has been hampered by remaining uncertainties about its pharmacodynamics and the methods used to probe its effects in the human brain. Using a dose-response design (9, 18 and 36 IU), we demonstrate that intranasal oxytocin-induced changes in local regional cerebral blood flow (rCBF) in the amygdala at rest, and in the covariance between rCBF in the amygdala and other key hubs of the brain oxytocin system, follow a dose-response curve with maximal effects for lower doses. Yet, the effects on local rCBF might vary by amygdala subdivision, highlighting the need to qualify dose-response curves within subregion. We further link physiological changes with the density of the oxytocin receptor gene mRNA across brain regions, strengthening our confidence in intranasal oxytocin as a valid approach to engage central targets. Finally, we demonstrate that intranasal oxytocin does not disrupt cerebrovascular reactivity, which corroborates the validity of haemodynamic neuroimaging to probe the effects of intranasal oxytocin in the human brain. Data availability: Participants did not consent for open sharing of the data. Therefore, data can only be accessed from the corresponding author upon reasonable request Graphical Abstract: ga1 Highlights: Lower doses of oxytocin produce greater decreases in amygdala perfusion at rest. Dose-response to oxytocin in the amygdala should be qualified by subregion. Intranasal oxytocin is likely a valid approach to engage central oxytocin targets. Intranasal oxytocin does not disrupt cerebrovascular reactivity.